Lack of a Clear Behavioral Phenotype in an Inducible FXTAS Mouse Model Despite the Presence of Neuronal FMRpolyG-Positive Aggregates - Haify, Saif N.; Mankoe, Ruchira S. D.; Boumeester, Valerie; van der Toorn, Esmay C.; Verhagen, Rob F. M.; Willemsen, Rob; Hukema, Renate K.; Bosman, Laurens W. J. (Frontiers in Molecular Biosciences, 2020)
Fragile X-associated tremor/ataxia syndrome (FXTAS) is a rare neurodegenerative disorder caused by a 55–200 CGG repeat expansion in the 5′ untranslated region of the Fragile X Mental Retardation 1 (FMR1) gene. FXTAS is characterized by progressive cerebellar ataxia, Parkinsonism, intention tremors and cognitive decline. The main neuropathological hallmark of FXTAS is the presence of ubiquitin-positive intranuclear inclusions in neurons and astrocytes throughout the brain. The molecular pathology of FXTAS involves the presence of 2 to 8-fold elevated levels of FMR1 mRNA, and of a repeat-associated non-AUG (RAN) translated polyglycine peptide (FMRpolyG). Increased levels of FMR1 mRNA containing an expanded CGG repeat can result in cellular toxicity by an RNA gain-of-function mechanism. The increased levels of CGG repeat-expanded FMR1 transcripts may create RNA foci that sequester important cellular proteins, including RNA-binding proteins and FMRpolyG, in intranuclear inclusions. To date, it is unclear whether the FMRpolyG-positive intranuclear inclusions are a cause or a consequence of FXTAS disease pathology. In this report we studied the relation between the presence of neuronal intranuclear inclusions and behavioral deficits using an inducible mouse model for FXTAS. Neuronal intranuclear inclusions were observed 4 weeks after dox-induction. After 12 weeks, high numbers of FMRpolyG-positive intranuclear inclusions could be detected in the hippocampus and striatum, but no clear signs of behavioral deficits related to these specific brain regions were found. In conclusion, the observations in our inducible mouse model for FXTAS suggest a lack of correlation between the presence of intranuclear FMRpolyG-positive aggregates in brain regions and specific behavioral phenotypes.